Age and Parity in the Incidence Of Primary Post Partum Hemorrhage at Panembahan Senopati Hospital, Bantul Yogyakarta - Vina Anggraini (Berkala Kedokteran, 2022)
Post partum hemorrhage is the main cause of 150,000 maternal deaths every year in the world and almost 4 out of 5 deaths due to postpartum hemorrhage occur within 4 hours after delivery. The direct causes of maternal death in Indonesia are bleeding 45.20%, eclampsia 12.90%, abortion complications 11.10%, postpartum sepsis 9.60%, prolonged labor 6.50%, anemia 1.60% and indirect causes of death. by 14, 10%. The purpose of this study was to determine the relationship between parity and age with the incidence of primary postpartum hemorrhage at Panembahan Senopati General Hospital. Analytical survey studies or case control surveys use a retrospective time approach. The sampling technique was purposive sampling with a ratio of the number of samples 1: 1, namely the case sample was 70 and the control sample was 70. The analysis technique was Chi Square. The results of Chi Square analysis showed that age and parity had a significant relationship with the incidence of primary postpartum hemorrhage, age (OR = 14.22 and p-value 0.000) while parity (OR 3.010 and p-value 9.643). It means that mothers with maternal age at risk (<20 and > 35 years) have a risk of 14.22 greater than the age not at risk (20-35 years). Mothers with parity at risk (1 and >3) had a 3.010 greater risk of primary postpartum hemorrhage than mothers with parity at no risk (2 and 3). This study concluded that there is a relationship between age and parity with the incidence of primary postpartum hemorrhage.